Design, Development, and Evaluation of the Low-Cost “SMART” Simulator for Postpartum Breast and External Genital Assessment - Herlyssa Herlyssa; Elly Dwi Wahyuni; Juli Oktalia (Indonesian Journal of Global Health Research, 2026)
Clinical skills training in postpartum breast and external genital assessment is a core competency in midwifery education. However, opportunities for direct practice with postpartum women are increasingly constrained by ethical considerations, patient safety, privacy concerns, and limited clinical exposure. Although simulation-based education has proven effective in addressing these challenges, affordable and context-specific simulators for postpartum assessment remain scarce, particularly in low- and middle-income educational settings. This study aimed to design, develop, and evaluate the feasibility and educational effectiveness of the low-cost “SMART” simulator for postpartum breast and external genital assessment in midwifery clinical skills training. A research and development (R&D) design was employed, comprising design, development, and evaluation phases. Validation by content experts, simulated patients, and lecturers was conducted using structured instruments, while educational effectiveness was assessed through a pretest–posttest clinical skills evaluation. The “SMART” simulator demonstrated high content validity, anatomical accuracy, and instructional relevance. Simulated patients reported very high acceptability, particularly regarding comfort, privacy, and ethical safety. Lecturers rated the simulator as highly feasible and appropriate for skills laboratories, OSCE preparation, and community-based learning. Students showed significant improvement in clinical skills following simulation-based training. Importantly, the simulator was developed using affordable, reusable materials, enabling repeated use without substantial financial burden. The low-cost “SMART” simulator is a valid, feasible, and effective simulation-based learning tool for postpartum breast and external genital assessment. Its affordability and adaptability support equitable access to high-quality clinical skills training while maintaining ethical standards and patient safety.